The early discourse on knowledge ('Ilm) in the work of al-Shafi'i (150-204/767-820) - Muhamad Shukri, Abdul Salam (Bait al-Hikmah at Madinat al-Hikmah, 2008)
This article discusses the contribution of Imam al-Shafi'i to the theory and clear definition of "ilm (knowledge) and importance of Khabar al-wahid (information/report based on a single narrator).